Vulnerability and Adaptation to Climate Change: Analysis of Farmers in the Rio das Contas Hydrographic Basin - Nogueira, Victor Gaston (2020)
This paper aims to understand the vulnerability and the adaptation process of farmers in the Rio das Contas basin, located in the Brazilian Northeast region. The vulnerability was analyzed using indexes representative of its three dimensions: sensitivity, exposure, and adaptive capacity. To analyze the adoption of adaptation strategies, the Probit model was used. The main results indicated that the region has high levels of vulnerability, mainly due to the low values of adaptive capacity. The most relevant conditions for adaptation are related to the education level and the farmers´ agricultural training, as well as participation in irrigation projects, receiving technical assistance, geographic location, and degree of exposure to climate change. In this sense, public policies for the reduction of vulnerability should focus on strengthening regional socioeconomic conditions.